2012
DOI: 10.1007/s10633-012-9357-7
|View full text |Cite
|
Sign up to set email alerts
|

Objective assessment of the human visual attentional state

Abstract: Primary objective The purpose of this study was to develop an objective way to assess human visual attention using the alpha band component of the visual-evoked potential (VEP). Design and methods Six different attentional conditions were tested: eyes-open, eyes-closed, eyes-closed with backwards number counting, and three rapid serial visual presentation (RSVP) tasks. 18 visually-normal, young-adult subjects (ages 21 to 28 years) were tested binocularly at 1 meter for each condition on two separate days. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
69
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(77 citation statements)
references
References 47 publications
(79 reference statements)
6
69
2
Order By: Relevance
“…30,31 The system consists of a 17·15 (horizontal·vertical) degree display monitor for stimulus presentation, a second monitor for use by the experimenter for data viewing, and a computer for stimulus generation, analysis, and graphical display. The Diopsys system is available commercially and is approved by the Food and Drug Administration for both research and clinical use.…”
Section: Apparatusmentioning
confidence: 99%
“…30,31 The system consists of a 17·15 (horizontal·vertical) degree display monitor for stimulus presentation, a second monitor for use by the experimenter for data viewing, and a computer for stimulus generation, analysis, and graphical display. The Diopsys system is available commercially and is approved by the Food and Drug Administration for both research and clinical use.…”
Section: Apparatusmentioning
confidence: 99%
“…This comparison is presented in Figure 1. More recent studies have demonstrated that the level of alpha band activity was correlated with different attentional states: eyes-closed as compared to the eyes-open condition [27][28][29], eyes closed with increased attentional demand as compared to the eyes-closed condition [28,30], visual imagery [31] and visual attention during reading [32]. These studies revealed that changes in neuronal activity occurred and were related to the different attentional states, thus producing predictable changes in the relative alpha band power contributions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Willeford et al [28] used the above ideas and improved VEP hardware/software technology to assess normal human visual attention. They confirmed and extended Fuller's earlier findings in 18 visually-normal, young-adults.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations